Study Related to Awareness of People About the Significance of Public Health and Healthy Life - Singhal, Sandeep (Journal of Commerce and Trade, 2021)
Public health promotes and protects the health of the people and communities in which they live, study, work and play. Public health is the science of protecting and improving the lives of people and their communities. This work is accomplished by promoting a healthy lifestyle, disease research and injury prevention, detection, prevention and response to infectious diseases. Generally, public health is about protecting people’s health. These people may be as small as a region, or as large as a whole country or region of the world. Community specialists try to prevent problems from happening or occur through education programs, recommend policies, provide services and do research - unlike therapists such as doctors and nurses, who focus on treating people after illness or injury. Public health also works to reduce health inequalities. A large part of public health promotes healthy lifestyle, quality and accessibility. Awareness of the disease and its symptoms is essential for early detection and diagnosis. If members of the public know about the disease and its symptoms, they are more likely to take steps to prevent it from happening to them, or to go to a health care provider for a check-up.